Reimbursement of care does not equal the distribution of hospital resources: an explorative case study on a missing link among Dutch hospitals - van Leeuwen, L. V. L.; Mesman, R.; Berden, H. J. J. M.; Jeurissen, P. P. T. (BMC health services research, 2023)
Background Affordability and accessibility of hospital care are under pressure. Research on hospital care financing focuses primarily on incentives in the financial system outside the hospital. It is notable that little is known about (incentives in) internal funding in hospitals. Therefore, our study focuses on the budget allocation in hospitals: the distribution model. Based on our hypothesis that the reimbursement and distribution models in hospitals might interact, we gain knowledge about-, and insight into, the interaction of different reimbursement and distribution models used in Dutch hospitals, and how they affect the financial output of hospital care. Methods An online survey with 22 questions was conducted among financial senior management as an expert group in 49 Dutch hospitals. Results Ultimately, 38 of 49 approached experts fully completed the survey, which amounts to 78% of the hospitals we approached and 60% of all Dutch hospitals. The results on the reimbursement model indicate price * volume with adjusted prices above a maximum cap as the most common dominant contract type. On the internal distribution model, 75–80% of the experts reported incremental budgeting as the dominant budgeting method. Results on the interaction between the reimbursement and the distribution model show that both general and specific changes in contract agreements are only partially incorporated in hospital budgets. In 28 out of 31 hospitals with self-employed medical specialists, a relation is reported between the reimbursement model and the contracts with the Medical Consultant Group(s) in which the medical specialists are united. Conclusions Our results in Dutch setting indicate a limited interaction between the reimbursement model and the distribution model. This lack of congruence between both models might limit the desired effects of incentives in contractual agreements aimed at the financial output. This applies to different reimbursement and distribution models. Further research into the various interactions and incentives, as visualized in our conceptual framework, could result in evidence-based advice for achieving affordable and accessible hospital care.